The Democratic Party and the gubernatorial election of 1876 in South Carolina. - Ginsberg, Betsy, 1943- (My University, 1968)
Contents include: the background of reconstruction and the beginning of democratic reorganization, the struggle to reorganize the democratic party, democratic campaign tactics, and the election and the dual government.
146 leaves ; 29 cm.
Keywords: Reconstruction --South Carolina.